Improving Speaking Ability Using Comic Strips Media for Class Xi Students MAN 3 Langkat Plus Keterampilan - Yusuf, Nazly; Sembiring, Puan Suri Mira Annisa (Universitas Negeri Medan, 2023)
This research was motivated by the low ability of students at MAN 3 Langkat Plus Keterampilan in speaking English. The purpose of this study is to improve speaking skills by using Comics Strips media in learning English. This research method uses Class Action Research (CAR) which is carried out in several stages, namely: (1) planning (planning), (2) action (acting), (3) observation (observing), (4) reflection (reflecting). The subjects of this study were students of Class XI MAN 3 Langkat Plus Keterampilan with a total of 35 people. The instruments used were observation sheets to observe student activities, questionnaires and speaking assessment sheets to measure learning achievement. Based on the results obtained during the implementation of classroom action research, it shows that comic strip media is very relevant and very well used in learning English to improve speaking skills. In the first cycle, the average speaking ability score was 75.55, then in the second cycle, it was 85.00. In cycle III the average value of students' speaking ability reached 90.00 to 92.00. Thus, it can be concluded that the use of comic strips learning media in learning English can improve students' speaking skills.